Vegetation index and spectral linear mixing model for monitoring the Pantanal region - Shimabukuro, Yosio Edemir; Novo, Evlyn Morais; Ponzoni, Flávio Jorge (Pesquisa Agropecuaria Brasileira, 1998)
This paper presents the contribution of the normalized difference vegetation index (NDVI) and the fraction images derived from linear mixing model for monitoring the dynamic of the land cover in the Pantanal region. The vegetation index and the vegetation, soil, and shade or water fraction images were derived from Landsat TM (Thematic Mapper) digital data acquired over the alto Taquari (MS) region, on December 22, 1992 (dry season) and on March 12, 1993 (rainy season). These images permitted to analyze the land cover in this region for the image dates, as well as to detect changes occurred during the period of image acquisition. The results indicated an apparent higher sensitivity of vegetation fraction image to land cover variation when compared to vegetation index image. The radiometric rectification method presented a good performance, indicating that the selected dark and bright targets in the images have not changed in the interval between dates of image acquisition.